Effects of foliar application of potassium orthophosphate on grain yield and kernel quality of Wheat (Triticum aestivum) under terminal heat stress (Bangladesh Journal of Agricultural Research, 2014)
A field experiment was conducted at Bangladesh Agricultural Research Institute (BARI) farm, Gazipur to evaluate the effect of foliar application of potassium orthophosphate on grain yield and kernel quality of wheat under the terminal heat stress imposed by late sowing for two consecutive years (2008-09 and 2009-10). Five combinations of foliar applications of potassium orthophosphate and Tilt were tested on three wheat varieties, namely Kanchan, Shatabdi, and Prodip. The result indicated that foliar application of potassium orthophosphate was effective in increasing SPAD value (Measure of leaf chlorophyll content) and leaf area of all the wheat varieties, whereas Tilt application was effective only in Kanchan. The grain size of wheat in terms of 1000-grain weight was improved and thereby contributed to grain yield. Also the foliar application of potassium orthophosphate decreased the number of immature, smaller and deformed kernel, and thus improved the kernel quality. Two foliar sprays of 0.1% potassium orthophosphate solution at 70 DAS (Days after sowing) and 80 DAS performed better results than other applications. There were varietal differences in response to foliar treatments and the variety Prodip and Shatabdi were more responsive to potassium orthophosphate compared to Kanchan. Potassium orthophosphate could be suggested to improve grain yield and kernel quality of wheat under terminal heat stress condition. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20144 Bangladesh J. Agril. Res. 39(1): 67-77, March 2014